DUKUNGAN KESEHATAN JIWA DAN PSIKOSOSIAL (DKJPS) DI MASA PANDEMI COVID-19 SEBAGAI BAKTI NGUDIA UNTUK MADURA - Faisal Amir; Zakkiyatus Zainiyah; Ulva Noviana; M. Hasinuddin (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2022)
Severe acute respiratory syndrome corona virus 2 (SARSCOV-2) or more familiarly known as Coronavirus disease 2019 (Covid-19) is a worldwide epidemic that causes chaos in various aspects of life. The impact of COVID-19 is not only felt physically and biologically, but can also have a psycho, social, cultural, economic, political and spiritual impact. In general, the perspective of the Madurese community is divided into two groups, namely people who believe and accept the existence of COVID-19 and people who refuse, do not believe and are ignorant. In the first group, the public really understands well the Covid-19 phenomenon and adheres to prevention protocols and everything related to government programs in preventive efforts. However, in the second group, people have a tendency to distrust the existence of COVID-19 and have low adherence to health protocols. Meanwhile, the special character of the Madurese community is very high obedience, one of which is applied through a philosophy with the term "ngabuleh" especially to the kyai or teacher of the Koran. This is a potential space that can be empowered so that in the future all forms of information that support the welfare of the health sector can be accepted and applied by the Madurese community. One of the strategies is through training on mental health and psychosocial support (DKJPS). The method used in the implementation of community service starts from the DKJPS training, the application by the participants and their families for 8 weeks, then evaluation of the implementation in a formative and summative manner. The result is that the DKJPS training and application during the Covid-19 pandemic tends to be able to change people's behavior in a more constructive direction in the health sector. Several applications have been implemented well and are expected to continue to run, while some DKJPS applications still require internalization and collaboration with many parties so that healthy messages are conveyed in a persuasive and easy manner by the Madurese community who are thick with culture and spirituality.